Human intestinal acyl-CoA synthetase 5 is sensitive to the inhibitor triacsin C - Kämmerer-Gaßler, Elke; Peuscher, Anne; Reinartz, Andrea; Liedtke, Christian; Weiskirchen, Ralf; Kopitz, Jürgen; Gassler, Nikolaus (World journal of gastroenterology, 2011)
Aim: To investigate whether human acyl-CoA synthetase 5 (ACSL5) is sensitive to the ACSL inhibitor triacsin C. Methods: The ACSL isoforms ACSL1 and ACSL5 from rat as well as human ACSL5 were cloned and recombinantly expressed as 6xHis-tagged enzymes. Ni2+-affinity purified recombinant enzymes were assayed at pH 7.5 or pH 9.5 in the presence or absence of triacsin C. In addition, ACSL5 transfected CaCo2 cells and intestinal human mucosa were monitored. ACSL5 expression in cellular systems was verified using Western blot and immunofluorescence. The ACSL assay mix included TrisHCl (pH 7.4), ATP, CoA, EDTA, DTT, MgCl2, [9,10-3H] palmitic acid, and triton X-100. The 200 μL reaction was initiated with the addition of solubilized, purified recombinant proteins or cellular lysates. Reactions were terminated after 10, 30 or 60 min of incubation with Doles medium. Results: Expression of soluble recombinant ACSL proteins was found after incubation with isopropyl beta-D-1-thiogalactopyranoside and after ultracentrifugation these were further purified to near homogeneity with Ni2+-affinity chromatography. Triacsin C selectively and strongly inhibited recombinant human ACSL5 protein at pH 7.5 and pH 9.5, as well as recombinant rat ACSL1 (sensitive control), but not recombinant rat ACSL5 (insensitive control). The IC50 for human ACSL5 was about 10 μmol/L. The inhibitory triacsin C effect was similar for different incubation times (10, 30 and 60 min) and was not modified by the N- or C-terminal location of the 6xHis-tag. In order to evaluate ACSL5 sensitivity to triacsin C in a cellular environment, stable human ACSL5 CaCo2 transfectants and mechanically dissected normal human intestinal mucosa with high physiological expression of ACSL5 were analyzed. In both models, ACSL5 peak activity was found at pH 7.5 and pH 9.5, corresponding to the properties of recombinant human ACSL5 protein. In the presence of triacsin C (25 μmol/L), total ACSL activity was dramatically diminished in human ACSL5 transfectants as well as in ACSL5-rich human intestinal mucosa. Conclusion: The data strongly indicate that human ACSL5 is sensitive to triacsin C and does not compensate for other triacsin C-sensitive ACSL isoforms.
Gesehen am 30.06.2022